Clinical profile and outcome of suspect pediatric COVID-19 patients: Experience from a COVID hospital - Dr. Surabhi Chandra; Dr. Gunjan Kochar; Dr. Lahar Sahai; Dr. Rahul Jaiswal; Dr. Akansha Bajwa (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: The Indian Council of Medical Research (ICMR) has given clinical criteria for suspecting COVID-19 in the Indian population and admissions to hospitals have been based on the above criteria. Aim - To study the clinical profile and outcomes of children suspected to have COVID-19 infection (based on ICMR criteria) admitted to a designated COVID hospital of North India.Methods: This was an observational study done in a COVID hospital of North India from April to June 2020. All children </= 18 years of age (including newborns), fulfilling the ICMR criteria and suspected to be COVID infected, from the screening area, were enrolled in the study. Demographic, clinical, laboratory, treatment details, and the final outcome were recorded on a pre-designed data collection proforma. Data was later entered into an MS-EXCEL 2013 spreadsheet and was analyzed using the Epi-info software version 7.2.2.Results: Of the 21 admissions (7 newborns and 14 children>1 month of age) occurring in the COVID suspect ward during the study period, only 1 patient with a positive history of contact, was found to be COVID positive. The mean age of presentation was 10.27 years (Range 0.8-17; SD 7.83). Four children (4/14 = 28.5%) children were admitted on the basis of having symptoms of SARI (Severe Acute Respiratory infection). One patient took leave against medical advice (LAMA) after his RT-PCR report came negative.Conclusion: The majority of children admitted as per the testing criteria were found to be COVID negative.